Plasma fibrinogen as prognostic predictor in patients with metastatic renal cell carcinoma receiving target therapy - Wang, Lihe; Cai, Wen; Kong, Wen; Zhang, Jin; Chen, Yonghui; Huang, Jiwei; Huang, Yiran (Translational Cancer Research, 2018)
Background: The purpose of this work was to detect the influence of plasma fibrinogen level on the prognosis of patients with metastatic renal cell carcinoma (mRCC) before treatment of targeted therapy. Methods: We identified mRCC patients who received first-line therapy of sorafenib or sunitinib between January 2006 to December 2016 in Renji Hospital affiliated to Shanghai Jiao Tong University School of Medicine. Kaplan-Meier method was used to estimate the progression-free survival (PFS) and overall survival (OS); log-rank test was used to compare the survival outcomes between patients with low and high fibrinogen level; and cox proportional hazard regression model was used to estimate the prognostic value. Prognostic accuracy was determined using Harrell concordance index (C-index) and receiver operating curve (ROC) analysis. Results: Patients with high fibrinogen level both had significantly shorter median PFS (6 vs. 15 months, P